2014
DOI: 10.1002/ajh.23772
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of acute myeloid leukemia with myelodysplasia‐related changes: A retrospective analysis in a cohort of Chinese patients

Abstract: We retrospectively analyzed 449 patients with AML under the WHO classification of AML 2008 and probed implications of this classification in diagnosis and treatment of acute myeloid leukemia with myelodysplasiarelated changes (AML-MRC) among them. The clinical presentations, biological features, treatments, and prognosis of patients diagnosed with AML-MRC were analyzed and compared with those of AML not otherwise specified (AML-NOS). In all patients, 115 (25.6%) were diagnosed as AML-MRC including 64 males and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 16 publications
(28 reference statements)
6
42
0
2
Order By: Relevance
“…It is also reported that the genes with the highest frequencies of mutation in AML‐MRC were ASXL1, TP53, RUNX1, and DNMT3A, of 21%, 28%, 12%, and 9%, which were predicted to a poor prognosis. The CR rate achieved in patients treated with the IA/DA regimen for induction chemotherapy was 63.6%, which was significantly lower than that achieved in the AML‐NOS patients (77.5%) . The 3 + 7 regimen did not achieve satisfactory results, which was the same as the results in our study.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It is also reported that the genes with the highest frequencies of mutation in AML‐MRC were ASXL1, TP53, RUNX1, and DNMT3A, of 21%, 28%, 12%, and 9%, which were predicted to a poor prognosis. The CR rate achieved in patients treated with the IA/DA regimen for induction chemotherapy was 63.6%, which was significantly lower than that achieved in the AML‐NOS patients (77.5%) . The 3 + 7 regimen did not achieve satisfactory results, which was the same as the results in our study.…”
Section: Discussionsupporting
confidence: 69%
“…Compared with 187 cases of AML‐NOS, Xiao‐Qian Xu et al reported that markedly lower WBC counts and hemoglobin were observed in AML with MLD and MDS‐related cytogenetic abnormality, 36.5% of which had a complex karyotype. It is also reported that the genes with the highest frequencies of mutation in AML‐MRC were ASXL1, TP53, RUNX1, and DNMT3A, of 21%, 28%, 12%, and 9%, which were predicted to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis is determined by underlying cytogenetic and molecular abnormalities. 42,43 What are the possibilities in the case a patient is classified as unfit or will not likely benefit from dose-intensive chemotherapy? LDAC (20 mg SC 23 for 10 days for 4-6 weeks) is quite commonly used in these patients in some countries but is less popular in other countries.…”
Section: Comments About Patientmentioning
confidence: 99%
“…3,4 Although the prognostic impact of dysplasia in AML is a matter of debate, [3][4][5][6][7][8][9][10][11] the presence of dysplasia is a negative independent factor for achieving complete remission (CR) after induction chemotherapy. In the subgroup analyses, upfront HCT had a significantly reduced incidence of leukemia-related mortality among patients aged between 60 and 70 years, those with a lower white blood cell count at diagnosis (<3000/μL), and poor cytogenetic risk, and those who received myeloablative conditioning and cord blood transplantation.…”
mentioning
confidence: 99%
“…In the subgroup analyses, upfront HCT had a significantly reduced incidence of leukemia-related mortality among patients aged between 60 and 70 years, those with a lower white blood cell count at diagnosis (<3000/μL), and poor cytogenetic risk, and those who received myeloablative conditioning and cord blood transplantation. [4][5][6]12 Even if CR is achieved, the duration of CR is usually short during post-remission chemotherapy, and the number of long-term disease-free survivors remains limited. Upfront HCT contributed to the reduced incidence of leukemia-related mortality after HCT.…”
mentioning
confidence: 99%